1988
DOI: 10.1212/wnl.38.1.114
|View full text |Cite
|
Sign up to set email alerts
|

Palsy of upward and downward saccadic, pursuit, and vestibular movements with a unilateral midbrain lesion

Abstract: Upward and downward gaze palsy was measured by a magnetic search coil technique and correlated with neuropathologic findings in a patient with a unilateral midbrain infarct. Oculography demonstrated (1) saccadic palsy above primary position and slow, limited vertical saccades below; (2) low-gain, restricted vertical pursuit; and (3) low-gain, abnormal phase lead, and restricted range of the vertical vestibulo-ocular reflex (VOR). Bidirectional palsy of vertical saccades is attributed to unilateral loss of burs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
49
0
6

Year Published

1988
1988
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(58 citation statements)
references
References 0 publications
3
49
0
6
Order By: Relevance
“…The authors stated that a unilateral riMLF lesion may have disrupted bilateral upgaze excitatory and inhibitory inputs and unilateral downgaze excitatory inputs [1]. Ranalli et al [2] noted a case of paralysis of upward saccades, decreased amplitude and velocity of downward saccades and vertical smooth pursuit, as well as decreased gain and amplitude of the vertical ocular reflex. The neurophysiological examination demonstrated involvement of the right riMLF, a part of the right INC, and the NPC, but the posterior commissure tract was preserved.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors stated that a unilateral riMLF lesion may have disrupted bilateral upgaze excitatory and inhibitory inputs and unilateral downgaze excitatory inputs [1]. Ranalli et al [2] noted a case of paralysis of upward saccades, decreased amplitude and velocity of downward saccades and vertical smooth pursuit, as well as decreased gain and amplitude of the vertical ocular reflex. The neurophysiological examination demonstrated involvement of the right riMLF, a part of the right INC, and the NPC, but the posterior commissure tract was preserved.…”
Section: Discussionmentioning
confidence: 99%
“…The neurophysiological examination demonstrated involvement of the right riMLF, a part of the right INC, and the NPC, but the posterior commissure tract was preserved. The authors hypothesized that downward gaze fibers might partly decussate in the ventral posterior commissure and transverse the region of the opposite riMLF [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a clinical perspective, after muscimol injection our animals showed symptoms of gaze-paretic nystagmus (a position-dependent drift of the eye) in the vertical and torsional components (Ranalli et al 1988), a contralateral ocular tilt reaction (torsional tilt of the eyes) (Westheimer and Blair 1975), and rotatory spasmodic torticollis (ST) (Loher et al 2004). All of these deficits have long been associated with midbrain damage in humans (Bertrand et al 1978;Plant et al 1989;Raeva et al 1987;Vasin et al 1985) and the physiological relationship of the INC to the oculomotor components of these disorders was previously considered in detail elsewhere (Crawford and Vilis 1993;Fukushima 1987;Helmchen et al 1998;Ranalli et al 1988).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies showed that the mesencephalic interstitial nucleus of Cajal (INC) is the neural integrator for vertical and torsional components of eye movements (Crawford 1994;Crawford and Vilis 1993;Fukushima 1987;Fukushima et al 1990;Helmchen et al 1998;King et al 1981;Ranalli et al 1988). Similarly, single-unit recordings of the INC neurons showed saccade-related burst activity for up/down and torsional quick eye rotations (Helmchen et al 1996).…”
Section: Introductionmentioning
confidence: 99%